7+4n+6n=-13

Simple and best practice solution for 7+4n+6n=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+4n+6n=-13 equation:


Simplifying
7 + 4n + 6n = -13

Combine like terms: 4n + 6n = 10n
7 + 10n = -13

Solving
7 + 10n = -13

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 10n = -13 + -7

Combine like terms: 7 + -7 = 0
0 + 10n = -13 + -7
10n = -13 + -7

Combine like terms: -13 + -7 = -20
10n = -20

Divide each side by '10'.
n = -2

Simplifying
n = -2

See similar equations:

| 0.5+55=30 | | 7.5+0.02x=9.5+0.01x | | a-5b-3ac= | | f(-2)=2x+3 | | 5a-15+9=3a+29 | | 71+4n+4=-14n-15 | | 2m^2-28m+49=0 | | 6.44x+325=2500 | | 9*7+8*x-2=93 | | 2s+3t=43 | | 0*50*1-60-60*60*0+10= | | 2(6x-3)-3(x+2)=1 | | 7x+49=2 | | 3s+2t=37 | | -6r+24=-14-22+6r | | 2p+5q=17 | | 4x-(2x-1)=3 | | 2m+2=-8 | | 6.7-q=q | | -5p+24=-8(b-6)+6b | | 2/3-q=q | | 3/2-q=q | | 8(x+4)=2(x+34) | | 2+5n=4n-20 | | m-(-2)=3 | | 2(x-3)=66-6x | | 6-3n=5n+22 | | 142-4x=6-10x | | 7(2x-1)=-4(6-2x) | | X(25+10)=45 | | 90+0.3m=70+.5m | | 2x=3(1-x)-(x+1) |

Equations solver categories